The Woven EndoBridge for intracranial aneurysms: Radiological outcomes and factors influencing occlusions at 6 and 24 months - Alpay Kemal; Lindgren Antti; Rautio Riitta; Parkkola Riitta (SAGE PUBLICATIONS INC, 2022)
Purpose: To identify factors influencing short- and mid-term radiological outcomes of intracranial aneurysms (IAs) treated with the Woven EndoBridge (WEB).
Methods: A total of 112 patients were treated for IAs with the WEB in at our institution between 2013 and 2020. Patients with 6- and/or 24-months follow-up data were included in the study. Aneurysm occlusion was evaluated using the Raymond-Roy occlusion classification (RR). RR 1 and RR 2 were considered as adequate outcomes, while RR 3 inadequate.
Results: Data were available for 91 patients (56 females, 62%) at 6 months and 62 of those patients (39 females, 58%) at 24 months. The adequate occlusion (RR 1/RR 2) rate was 89% (n = 81/91) at the 6-months follow-up and 91% (n = 56/62) at the 24-months follow-up. The treatment-related morbidity rate was 4% (n = 4/91), and mortality rate was 1% (n = 1/91). The predictor for inadequate occlusion at the 6-months follow-up was the lobular shape of an aneurysm (p = .01). The aneurysm's height (p = .02), maximal diameter (p = .001), width (p = .002), aspect ratio (p = .03), dome-to-neck ratio (p = .04), and lobular shape (p= .03) were predictive factors for inadequate occlusion at 24 months. All the thrombosed aneurysms (n = 3) showed unfavorable radiological outcomes and required re-treatment within 24 months. None of the patient-related factors were significant.
Conclusions: The WEB provides favorable occlusion rates and low complications for both ruptured and unruptured wide-necked IAs. Unfavorable radiological outcomes after WEB treatment may be related to aneurysm morphology and size.